Foreign Trade Policy in the Argentine Automotive Industry: An Analysis of the Business Power of its Actors and their Influence over the State (2002–15) - Perez Almansi, Bruno Sebastian (2023)
The article aims to analyse how the business power of actors in the Argentine automotive industry influenced the foreign trade policies relevant to the sector between 2002 and 2015. The research methods employed combine documentary sources, interviews with key informants and descriptive statistics. The overall findings show how automakers achieved considerable power in the first stage of the period, obtaining clear benefits in terms of foreign trade policy. However, macroeconomic and political changes in Argentina after 2008 had a negative impact on their business power, leading to their enjoying a reduced number of trade policy concessions.